RESPON KONSUMEN RITEL MELALUI FORMAT TOKO POP-UP DALAM MENINGKATKAN PENJUALAN - SUNYOTO, ERWIN (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Pop-up stores where retail brands occupy temporarily in place of the empty retail space is not something new. Pop-up shops allow visitors to have a unique brand experience, personalized interactions, and may be open in only one location and for a limited time, within a few days to one year. Therefore authors interested in writing more about the response of consumers to the existence in retail stores with pop-up format and its benefits in boosting sales. Pop-up stores must not only targeted to younger audiences, but could instead show a form of experience marketing that appeals to a wide age group of consumers. Consumer confidence about the novelty/unique pop-up store products affect the attitudes and intentions of protection against involvement in the pop-up store experience.